DINAMIKA PERILAKU PEMILIH NU; Pasang Surut Suara NU Pada Pemilu Paska Orde Baru - Ahmad Rofik (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
This paper will discuss the dynamics of voter behavior in elections NU post-new order which have ups and downs. But the post elections throughout the new order, the behavior of voters NU showed a trend of change. This paper discusses the dynamics of voter behavior in addition to NU in the new order post-election, also explains how the future of NU voter behavior in the era of liberal democracy. Before discussing the subject matter dynamics of voter behavior on election NU post-new order, will be given NU historical and political perspective on the new order.